Increasing momentum : - Rasmussen, Carolyn (Melbourne University press, 2004)
Momentum is your personal guidebook to the art and science of success. Momentary victories and small wins don't last, and the frustration of reclaiming that energy is real. This book shows you how to cultivate a different type of achievement – measureable, sustainable and constant. It's the difference between winning a battle and winning the war, and requires more than a single brilliant move